PENINGKATAN PRESTASI BELAJAR MELALUI PEMBERIAN BELAJAR TAMBAHAN PADA SISWA KELAS X PROGRAM KEAHLIAN JASA BOGA DI SMKN 6 PADANG - Asnimiarti, Asnimiarti (TINGKAP, 2016)
ABSTRACTThis study aims to determine whether the provision of additional learning can improve student achievement in the subjects of Continental Food Processing at students of Class X Hospitality Skills Program at SMK Padang 6. This study is a quasi-experimental research. The population in this study is all students of class X3 of Hospitality expertise program at SMK N 6 Padang which consists of 32 students. The sample in this study is collected by census or total sampling. Data collection instrument used in this study is the achievement test in the form of multiple choice objective tests. The data were analysed with T-Test formula. The results of this study indicate that there are significant differences in academic achievement between students who were given additional lessons and they were not given the additional lessons in subjects Continental Food Processing at students of Class X Hospitality Skills Program at SMK Padang 6.Keywords: Learning achievement, additional learning, hospitality